EFEKTIVITAS MUSIK GENRE JAZZ POP TERHADAP KONSENTRASI BELAJAR SISWA SMA NEGERI 3 TAMBUN SELATAN - Riska Azza Amellia; Arsyadani Hasanah; Christiney Permata Yaspis Tarigan; Farhan Saputra; Netty Merdiaty (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
Music is enjoyable for many people. It has also long been recognized as an element that can influence the learning atmosphere. Many students lack concentration in the learning process because they think about other things besides the lesson they are doing. The ability to concentrate is needed by students in the learning process. This study aims to determine whether jazz music can affect learning concentration in students. This study used an experimental research method, namely Quasi Experiment with One group Pretest-Posttest Design. A total of 10 participants were given a pre-test and post-test which then obtained the pre-test result was 12,600 and the post-test was 12,900. Based on the results of hypothesis testing, the results show that Ttabel is greater, this shows that jazz music has no effect in increasing the concentration of students of SMA Negeri 3 Tambun Selatan.